Research on Control Strategy of AC-DC-AC Substation Based on Modular Multilevel Converter. (8th November 2017) - Chang, Fei; Yang, Zhongping; Lin, Fei
Abstract : Significant disadvantages in power quality especially the unbalance problem and neutral sections restrict the evolution of conventional traction power supply system. A new traction power supply system based on three-phase to single-phase converter is studied, which can transfer active power from three-phase grid to single-phase catenary. One catenary section could be utilized in the new traction power supply system instead of the multiple split sections in conventional system. Three-phase to single-phase converter is the core equipment of new traction power system. MMC (modular multilevel converter) structure of AC-DC-AC substation is proposed in this paper. To solve the problem of the capacitor voltage balancing in MMC, a parallel sorting algorithm based on field programmable gate array (FPGA) is studied. And the correctness and effectiveness of the algorithm are verified by experiments. In addition, it is inevitable that the AC grid voltage will be unbalanced caused by the fault in the new system. Therefore, this paper focuses on the analysis of the effect of the unbalanced grid voltage on the operating characteristics of the MMC system. Finally, the correctness of the theoretical analysis is verified by simulation.